Banned Books (Dorling Kindersley, 2022)
Censorship of one form or another has existed almost as long as the written word, while definitions of what is "acceptable" in published works have shifted over the centuries, and from culture to culture. Banned Books explores why some of the world's most important literary classics and seminal non-fiction titles were once deemed too controversial for the public to read whether for challenging racial or sexual norms, satirizing public figures, or simply being deemed unfit for young readers. From the banning of All Quiet on the Western Front and the repeated suppression of On the Origin of the Species, to the uproar provoked by Lady Chatterley's Lover, entries offer a fascinating chronological account of censorship, and the astonishing role that some banned books have played in changing history. Packed with eye-opening insights into the history of the written word, and the political and social climate during the period of suppression or censorship, this is for anyone interested in literature, creative writing, politics, history, or law.